Ornate Dvarashakha (door jambs) - Temples of India Project Team (Jio Institute, 2024)
View of the entrance to the southern shrine, one of the three shrines in this temple, in the Neelkanth Mahadev Temple. The entrance is adorned with an ornate dvarashakha (door jambs). The ceiling of the passage that connects to the shrine is a flat ceiling with a lotus medallion. It has a depiction of Shiva and Parvati on the latatabimba (lintel) of the dvarashakaha. The pilasters at the entrance of the passage to the shrine are relatively simple compared to the central pillars of the mandapa (pillared hall).